Effects of CeO2 on the phase, microstructure and mechanical properties of Al2O3-ZrO2(CeO2) nanocomposite ceramics (AZC-NCs) by solid solution precipitation. Issue 23 (1st December 2022) - Yu, Wanjun; Zhang, Enliang; Yu, Yongdong; Li, Xiangming; Liu, Xudong; Yuan, Yuchen; Zheng, Yongting
Abstract: It is one of the most concerning issues to achieve fine nanostructures and a reasonable ZrO2 crystal structure in Al2 O3 –ZrO2 structural ceramics. Herein, Al2 O3 –ZrO2 (CeO2 ) nanocomposite ceramics (AZC-NCs) with different CeO2 contents were prepared by sintering Al2 O3 –ZrO2 (CeO2 ) supersaturated solid solution powders (AZC-SSSPs). The effects of CeO2 on the phase, microstructure, and mechanical properties of AZC-NCs were investigated systematically. During rapid solidification process, three phases of Al2 O3, ZrO2 and CeO2 are dissolved together and form AZC-SSSPs with regular spheres. After sintering, the AZC-SSSPs transform into two-phase structure and compact into AZC-NCs. The AZC-NCs show an intragranular/intercrystalline nanoprecipitation structure, and large amounts of ZrO2 in AZC-NCs remain in a tetragonal structure at room temperature because of the addition of CeO2 . Among the AZC-NCs, that with 6 mol% CeO2 shows the best mechanical properties with the highest values of strength and toughness: 865 ± 24 MPa and 8.4 ± 0.16 MPa·m 1/2 . Spark plasma sintering has no obvious influence on the microstructure and phase composition of AZC-NCs. This work provides guidance to optimize the microstructure and ZrO2 crystal structure of AZC-NCs.